Diode-pumped LiY0.3Lu0.7F4:Pr and LiYF4:Pr red lasers. (8th November 2016) - Lyapin, A A; Gorieva, V G; Korableva, S L; Artemov, S A; Ryabochkina, P A; Semashko, V V
Abstract: The laser quality LiY0.3 Lu0.7 F4 :Pr and LiYF4 :Pr fluoride single crystals were grown in Kazan University by the Bridgeman technique. Spectral-kinetic properties of LiY0.3 Lu0.7 F4 :Pr and LiYF4 :Pr crystals have been investigated. For the first time, laser oscillations of LiY0.3 Lu0.7 F4 :Pr crystal have been obtained on 3 P0   →   3 F2 transitions ( λ   =  640 nm) under multimode diode pumping at 442 nm, with a slope efficiency of 9 %. Also, continuous-wave lasing has been obtained for LiYF4 :Pr crystal at 640 nm under the same pumping condition with a slope efficiency of 8.5%. The maximum output power of 340 mW has been achieved for both crystals.